ENERGY CONSUMPTION PROJECTION IN YOGYAKARTA CITY - Septiana Ria Prihandita; Deendarlianto -; Rachmawan Budiarto (ASEAN Journal of Systems Engineering, 2015)
Availability of energy is an important aspect for the success of regional development. Yogyakarta city does not have any non-renewable energy sources such as liquid fossil fuels, coal and natural gas. Consequently,these energy must be supplied from other provinces. The renewable energy potential in Yogyakarta city is not being utilized yet. Final energy consumption continues to rise along with population and economic growth.Energy planning and development need be done carefully in order to ensure the energy sustainability. This study aim to provide long-term projections in 2012-2025 periods on energy balance, energy demand andsupply based on energy reserves and current condition in order to meet energy elasticity to less than 1. Energy demand projection is calculated based on trend forecasting analysis by LEAP (Long-range Energy Alternatives Planning System).This result shows that the highest energy user sector in Yogyakarta city period 2012-2025 is transportation sector and the highest of energy demand by type is electricity and gasoline. Renewable energypotential such as biogas, solar energy, biomass and biodiesel (from using vegetable oil waste) could be developed in Yogyakarta city. Using biodiesel and solar energy could decrease diesel fuel and electricity.According to the baseline scenario, CO2 emission reached 2,176,182 tons, the first alternative scenario reached 1,925,089 tons and the second alternative scenario reached 1,877,839. Investment cost to build renewable energy in the baseline scenario reached USD 42,045 – USD 546,585. Investment cost to build renewable energy in the first alternative scenario reached USD 10,470,775 – USD 31,002,775. Investment cost to build renewable energy in the second alternative scenario reached USD 31,641,925 - USD 52,173,925.